2020
DOI: 10.21203/rs.3.rs-26499/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incidence and determinants of mortality among HIV infected adult patients on antiretroviral therapy in Ethiopia: A systematic review and Meta-analysis

Abstract: Background Antiretroviral therapy has been highly associated with reduction in the incidence of mortality in HIV/AIDS patients over time. However, there is a regional variation in the extent of reducing the incidence of mortality in many developing countries including Ethiopia. Hence, this study was conducted to generate summary evidences-based data for incidence of mortality and determinants of mortality. Methods Articles were comprehensively searched on Pub Med, Google Scholar, Cochrane library, Scopus, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Might be due to the presence of invasive diagnostic modalities in specialized referral hospital [13] But less than the study done in south Tigray region, Addis Abeba and Sidama [10,14,15] Might be due to patients coming late to health care service with opportunistic infection before anti-retroviral treatment initiation [16,17].Provisions of cotrimoxazole prophylaxis to the eligible anti-retro viral treatment initiated patients indicated protective to the opportunistic infections than the patients who have no cotrimoxazole prophylaxis was in line with [2,[18][19][20][21]. Might be associated with the treatment of diseases indicating the WHO clinical stage of ART administration and the continuation of prophylaxis as the national ART guideline recommendation reduce opportunistic infections [20] Patients who have base line CLINICAL stage 3 and stage 4 developed opportunistic infections than patients who have BASELINE clinical stage 1and stage 2 condition was in line with the study [14,18,[22][23][24][25] This might be due to low CD4 count to protect the disease, different studies indicated patients who have lowCD4 count vulnerable to opportunistic infections[26-29] Immediate diagnosis and treatment of the opportunistic diseases at the initiation of anti-retro viral treatment, intensive screening eligible patients for supportive treatment and anti-retro viral treatment drug adverse effect is reduce the occurrence of opportunistic diseases [18,30,31].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Might be due to the presence of invasive diagnostic modalities in specialized referral hospital [13] But less than the study done in south Tigray region, Addis Abeba and Sidama [10,14,15] Might be due to patients coming late to health care service with opportunistic infection before anti-retroviral treatment initiation [16,17].Provisions of cotrimoxazole prophylaxis to the eligible anti-retro viral treatment initiated patients indicated protective to the opportunistic infections than the patients who have no cotrimoxazole prophylaxis was in line with [2,[18][19][20][21]. Might be associated with the treatment of diseases indicating the WHO clinical stage of ART administration and the continuation of prophylaxis as the national ART guideline recommendation reduce opportunistic infections [20] Patients who have base line CLINICAL stage 3 and stage 4 developed opportunistic infections than patients who have BASELINE clinical stage 1and stage 2 condition was in line with the study [14,18,[22][23][24][25] This might be due to low CD4 count to protect the disease, different studies indicated patients who have lowCD4 count vulnerable to opportunistic infections[26-29] Immediate diagnosis and treatment of the opportunistic diseases at the initiation of anti-retro viral treatment, intensive screening eligible patients for supportive treatment and anti-retro viral treatment drug adverse effect is reduce the occurrence of opportunistic diseases [18,30,31].…”
Section: Discussionsupporting
confidence: 60%
“…The majority of 186 (59%) were female. The median age was 35 years with an interquartile (IQR) of (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) and the median duration of antiretroviral treatment were 42 months with IQR of (32-56). The overall prevalence of opportunistic infections was estimated 21.9% with (95% con dence interval (CI,).Isoniazid preventive therapy coverage was 76.8%.Using logistic regression multivariate analysis with SPSS Cotrimoxazol prophylaxis (AOR=0.24,95% CI = 0.07-0.86)and base line CLINICAL stage(AOR=2.9,95%CI=1.58-5.34),were independent predictors of opportunistic infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation